Analisis Hubungan Minat Belajar Terhadap Kemampuan Penalaran Matematis Siswa Kelas X - Olenggius Jiran Dores; Nurapni Sopia; Aming Aming (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
This study aims to analyze the interest in learning towards students' mathematical reasoning abilities in exponential material for class X SMAN 4 Sintang. From the results of research that has been done by the author, the factor that causes low mathematical reasoning is the lack of student interest in learning. The research aims to analyze interest in learning and mathematical reasoning abilities. The method used by researchers in this research is descriptive with a qualitative approach. The object of this research was class X students with a total of 15 participants. The data collection tools used in this research are student activity observation sheets, questionnaire sheets, and test question sheets. The results of research on class X students of SMAN 4 Sintang are in the very low category. This indicates that students' interest in learning exponential material with an average yield of 10.82%. While students' mathematical reasoning abilities were 51.66%. Factors supporting students' interest in mathematical reasoning abilities were motivation, encouragement from teachers and parents, association and discipline, inhibiting factors, namely learning that had not used learning media, students were busy themselves. Efforts made by the teacher to overcome the inhibiting factors of student interest in students' mathematical reasoning abilities are the teacher providing motivation to students, providing learning media, encouraging students to prepare themselves in the learning that will take place.